2012
DOI: 10.1111/jop.12008
|View full text |Cite
|
Sign up to set email alerts
|

Salivary markers of oxidative stress are related to age and oral health in adult non‐smokers

Abstract: Age as a significant contributor to the variance should be taken into account in studies focusing on salivary markers of oxidative stress. The relationship between PBI and salivary TBARS confirms results from previous studies. In addition, our results show that the association is age independent. Negative association between the CI and AOPPs might be related to recent findings that AOPP might be actually a marker of non-enzymatic antioxidant status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
(23 reference statements)
0
25
2
1
Order By: Relevance
“…Oxidative stress may be the result of an increase in free radical production or a decrease in protective antioxidant mechanisms . Although some studies have demonstrated an association between salivary markers of oxidative stress and periodontal status, no significant difference was observed in the salivary concentration of TBARSs among the groups in the present study . It is possible to suggest that this result is because of a compensatory effect of the antioxidant capacity of saliva, which involves the action of different mechanisms, such as antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase, which are involved in the neutralization of free radicals …”
Section: Discussioncontrasting
confidence: 79%
“…Oxidative stress may be the result of an increase in free radical production or a decrease in protective antioxidant mechanisms . Although some studies have demonstrated an association between salivary markers of oxidative stress and periodontal status, no significant difference was observed in the salivary concentration of TBARSs among the groups in the present study . It is possible to suggest that this result is because of a compensatory effect of the antioxidant capacity of saliva, which involves the action of different mechanisms, such as antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase, which are involved in the neutralization of free radicals …”
Section: Discussioncontrasting
confidence: 79%
“…Furthermore, findings on MDA levels were mostly obtained from serum and plasma. To the authors’ knowledge, only a few studies have focused on comparing MDA levels in the saliva of patients with periodontitis and controls 14,17,22‐28 . Moreover, although some of these studies showed significant differences in salivary MDA levels between patients with periodontitis and healthy controls or significant correlation between salivary MDA levels and periodontal parameters, 14,17,22,28 others did not 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, LPO was mainly investigated in patients with periodontitis to assess the role of OS in periodontal diseases 14‐17,22‐28 . A recent meta‐analysis showed that the conclusions of different studies on this subject remain controversial, possibly owing to study heterogeneity, such as design, sample size, and biomarker measurement methods 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations